Asesmen Siklus Keberadaan(Life Cycle assesment) Dalam Industri Kemasan - Triyanto Hadisoemarto (Balai Besar Kimia dan Kemasan, 1997)
Based on its breadth approach of the study, the life cycle assessment (LCA) concept can be used as a reliable management tool to develop a better understanding of the environmental aspects of the activities. The concept of LCA has been applied to a variety of products, processes and services for a number of reasons, such as organisation policy development, product improvement and waste management. This paper provides the basic concept of life cycle assessment and illustrates its application in the packaging industry.